Nontypeable Haemophilus influenzae infection of pulmonary macrophages drives neutrophilic inflammation in severe asthma. Issue 10 (30th May 2022) - Ackland, Jodie; Barber, Clair; Heinson, Ashley; Azim, Adnan; Cleary, David W.; Christodoulides, Myron; Kurukulaaratchy, Ramesh J.; Howarth, Peter; Wilkinson, Tom M. A.; Staples, Karl J.
Abstract: Background: Nontypeable Haemophilus influenzae (NTHi) is a respiratory tract pathobiont that chronically colonizes the airways of asthma patients and is associated with severe, neutrophilic disease phenotypes. The mechanism of NTHi airway persistence is not well understood, but accumulating evidence suggests NTHi can persist within host airway immune cells such as macrophages. We hypothesized that NTHi infection of pulmonary macrophages drives neutrophilic inflammation in severe asthma. Methods: Bronchoalveolar lavage (BAL) samples from 25 severe asthma patients were assessed by fluorescence in situ hybridisation to quantify NTHi presence. Weighted gene correlation network analysis (WGCNA) was performed on RNASeq data from NTHi‐infected monocyte‐derived macrophages to identify transcriptomic networks associated with NTHi infection. Results: NTHi was detected in 56% of BAL samples (NTHi+) and was associated with longer asthma duration (34 vs 22.5 years, p  = .0436) and higher sputum neutrophil proportion (67% vs 25%, p  = .0462). WGCNA identified a transcriptomic network of immune‐related macrophage genes significantly associated with NTHi infection, including upregulation of T17 inflammatory mediators and neutrophil chemoattractants IL1B, IL8, IL23 and CCL20 (all p  < .05). Macrophage network genes SGPP2 ( p  = .0221), IL1B ( p  = .0014) and GBP1 ( p  = .0477) were more highly expressed in NTHi+ BAL and moderately correlated with asthma duration ( IL1B ; rho = 0.41, p  = .041) and lower prebronchodilator FEV1/FVC% ( GBP1 ; rho = −0.43, p  = .046 and IL1B ; rho = −0.42, p  = .055). Conclusions: NTHi persistence with pulmonary macrophages may contribute to chronic airway inflammation and T17 responses in severe asthma, which can lead to decreased lung function and reduced steroid responsiveness. Identifying therapeutic strategies to reduce the burden of NTHi in asthma could improve patient outcomes. Abstract : Visualization of NTHi presence in the severe asthmatic airway demonstrates NTHi association with BAL macrophages, suggesting a mechanism of airway persistence. Modeling NTHi–macrophage interactions in vitro identifies upregulation of macrophage T17 responses. NTHi modulation of airway inflammation can be detected in vivo, with BAL macrophage gene expression correlated with decreased lung function in NTHi+ patients and increased neutrophilic inflammation detected in those with NTHi airway presence, suggesting that NTHi‐infected macrophages may contribute to the complex chronic inflammatory environment in asthma.Abbreviations: BAL, bronchoalveolar lavage; CXCL8, C‐X‐C Motif Chemokine Ligand 8; GBP1, guanylate binding protein 1; IL1B, interleukin 1 beta; NTHi, nontypeable Haemophilus influenzae; RNA‐Seq, RNA sequencing; SGPP2, sphingosine‐1‐phosphate phosphatase 2